SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KARYAWAN TERBAIK DITOKO KEAN DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Tyoso, Bestanto Atijaya; Diartono, Dwi Agus (Elkom: Jurnal Elektronika dan Komputer, 2023)
Selection of the best employees is a semi-structured matter that can be scheduled every month or year. It is not uncommon for companies to determine the best employees not in accordance with the company's assessment. Kean shops still use the manual method and often do not meet the criteria set by the company. By making the best employee decision support system in a grocery store using the simple additive weighting method. assist managers in making the best employee decisions and admins in editing, deleting and adding values in each of the existing criteria and directly connected to the system database. This system was developed using the Visual Studio Code website, PHP, CSS, XAMPP V3.3.0 and MySQL. The method used in this decision support system is simple additive weighting (SAW). With this website, decision making is more structured and value data for each employee can be stored in a database. The results of this decision support system will simplify the process of determining the best employees and this system does not need to use manual calculations and is far more efficient.